Theologie als Professionstheorie für Religionslehrkräfte - Dressler, Bernhard (Österreichisches Religionspädagogisches Forum, 2023)
Friedrich Schleiermacher first understood theology as a ‚positive’ and ‚practical’ science. This – in modern terms – professional concept can also be understood as the basic expertise for teachers in religion education. It includes that the ‚sense and taste’ for religion or, in other words, the positively interpreted and reflected experiences of a participation in religion as a cultural praxis are constituting confessional religion instruction, and not theology as content or theological confessions.